Causes, Coping and Consequences of Stress at WorkCauses, Coping and Consequences of Stress at Work, edited by CooperCary L. and PayneRoy. Chichester, England: Wiley, 1988, 418 pp., $57.95, cloth. - Quick, James Campbell (Academy of Management Review, 1989)
The article reviews the book “Causes, Coping and Consequences of Stress at Work,” edited by Cary L. Cooper and Roy Payne.